If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 49(x + 2) = 490 Reorder the terms: 49(2 + x) = 490 (2 * 49 + x * 49) = 490 (98 + 49x) = 490 Solving 98 + 49x = 490 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-98' to each side of the equation. 98 + -98 + 49x = 490 + -98 Combine like terms: 98 + -98 = 0 0 + 49x = 490 + -98 49x = 490 + -98 Combine like terms: 490 + -98 = 392 49x = 392 Divide each side by '49'. x = 8 Simplifying x = 8
| 21r+2=5 | | 9x-3=2x+46 | | 17h-10=75 | | 7+4x=10x-9 | | 10c+-24=6 | | 23+8b=-4.2 | | 2a-5a+11=2-3a+9 | | -6b+10=-14 | | 8x=60-4x | | 3x-1=243 | | 15=3y+6 | | 8x+3=5x-18 | | 1+2g=-7 | | 3.6y=5.4+3.3y | | 14+5x=2x-7(x+8) | | -3z+6=z | | 8x-(6x-5)=1 | | 2y-1=13 | | 7-2n=n-4 | | 4-x=-3 | | -4(x+2)=-3(x+5)-x | | 3(14x)=150+27x | | 500*25x=5000 | | 19t+-6=70 | | 4b-1=2(2b+3) | | -2x+-4=16 | | 8-(3+b)=b-4 | | 7q+5=68 | | 3t+8(2t-6)=2+14t | | -6+2x=-10 | | 6x+2x-11=-2(2x-3)-x | | 5(15x+50)=925 |